Competing risk analysis of dexmedetomidine use and postoperative outcomes in non-traumatic subarachnoid hemorrhage patients - Tian-hua Lin; Zong-jie Wang; Yun-yun Tu; Mu-hua Dong; Ting Qiu; Wen-jie Lan; Ying Chen (European Journal of Medical Research)
Abstract Background Dexmedetomidine is widely used in critically ill patients, but its effects on postoperative outcomes in non-traumatic subarachnoid hemorrhage (SAH) patients remain unclear. This study focuses on exploring the impact of dexmedetomidine on postoperative respiratory failure (RF) and in-hospital mortality. Methods The data were downloaded from the Medical Information Mart for Intensive Care (MIMIC-IV) database, including 817 non-traumatic SAH patients. Propensity score matching (PSM) was performed. Multivariable logistic regression, sensitivity, interaction, and subgroup analyses were used to examine the association between dexmedetomidine use and RF or in-hospital mortality. A competing risk model was employed, with RF defined as the event of interest and in-hospital mortality as the competing event, to evaluate the survival probabilities for both outcomes. Results Dexmedetomidine use was a risk factor for RF but a protective factor for in-hospital mortality both pre-/post-PSM (p < 0.05). The protective effect of dexmedetomidine on mortality was more pronounced in younger patients (≤ 62 years) and those without cerebrovascular disease. Competing risk analysis showed that even after adjusting for confounders, dexmedetomidine remained a significant protective factor for in-hospital mortality, but did not affect the incidence of RF. Conclusions Dexmedetomidine use in non-traumatic SAH patients significantly reduces in-hospital mortality but does not affect the incidence of postoperative RF. These findings highlight the importance of considering competing risks when evaluating the effects of dexmedetomidine on postoperative outcomes.